P‐182: Long‐Life Green Phosphorescent OLED with Light‐Emitting Layer Formed by Two‐Source Evaporation Using Host Material with Novel Hetero Fused Ring. Issue 1 (29th May 2019) - Ohsawa, Nobuharu; Mitsumori, Satomi; Sasaki, Toshiki; Kido, Hiromitsu; Watabe, Takeyoshi; Inoue, Hideko; Seo, Satoshi; Yamazaki, Shunpei
Abstract : We developed an electron‐transport (ET) host material with a novel hetero fused ring which prolongs the lifetime of green phosphorescent organic light‐emitting diodes (OLEDs). We also developed a premixed host containing the ET host and a hole‐transport host. The use of the premixed host can facilitate production of the OLEDs.